Policy Formulation in Integrating Vocational Education Graduates with the Labor Market in Indonesia - Rahman, Abdul; Zebua, Winda Dwi Astuti; Satispi, Evi; Alan Kusuma, Andrean (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to analyze the policy formulation in integrating vocational education graduates with the labor market in Indonesia. The expected impact of this research is to improving quality of policy formulation in the universe of vocational education and to increasing the massive absorption of vocational education graduates with the labor market in Indonesia. The framework of policy formulation with the model of Political Administrative Program (PAP) which consists of the elements: concrete objectives, evaluative elements, operational elements, political-administrative arrangements, and procedural elements are used in this study. This research used a qualitative method with a phenomenological study. The results showed that the policy formulation in integrating vocational education graduates with the labor market in Indonesia is not fully optimal. there are some weaknesses that become critical notes such as: far gap between the projected proportion of job opportunities per year with the number of graduates in vocational education and training, lack of relevance of projections between Strategic Objective Performance Indicators (IKSS) and Program Performance Indicators (IKP) in the realm of courses and training, low projection target of increasing Program Performance Indicators (IKP) per year until 2024, synergy of stakeholders (including the world of work) in the Vocational High Schools development program is still lacking, and fragility of the substance of employment in Law of the Republic of Indonesia Number 11 of 2020.